Reconstructing Sharia Governance for Artificial Intelligence Adoption in Islamic Financial Institutions - Syahriyah Semaun (Journal of Islamic Economy, 2026)
Artificial intelligence (AI) is rapidly reshaping the operational and decision-making architecture of Islamic financial institutions (IFIs), yet governance mechanisms required to keep such technologies aligned with Shariah principles remain fragmented and under-theorized. This study reconstructs a Shariah governance framework for AI adoption across screening, credit-risk assessment, fatwa support, and internal audit functions in IFIs. Using a systematic literature review guided by the PRISMA protocol, twenty-five peer-reviewed journal articles and conference proceedings published between 2023 and 2026 were analyzed to map how existing scholarship conceptualizes the intersection of AI, Shariah supervisory boards, and Maqasid al-Shariah. The review identifies four recurring governance gaps: algorithmic opacity that undermines fatwa traceability, unclear allocation of liability between technology developers and Shariah boards, uneven regulatory harmonization across jurisdictions, and limited technical capacity within Shariah supervisory boards to audit machine-driven outputs. Building on these gaps, the study proposes a reconstructed governance model that embeds explainable-AI requirements, a dual-layer supervisory mechanism combining Shariah boards with dedicated AI governance committees, and Maqasid-based ethical checkpoints throughout the AI lifecycle. The findings contribute both theoretically to Islamic finance governance literature and practically to regulators and IFIs seeking to adopt AI without compromising Shariah legitimacy, transparency, and public trust in an increasingly digitalized financial ecosystem.